2013
DOI: 10.1007/s00221-013-3419-2
|View full text |Cite
|
Sign up to set email alerts
|

Cue integration and the perception of action in intentional binding

Abstract: ‘Intentional binding’ describes the perceived temporal attraction between a voluntary action and its sensory consequence. Binding has been used in health and disease as an indirect measure of awareness of action or agency, that is, the sense that one controls one’s own actions. It has been proposed that binding results from cue integration, in which a voluntary action provides information about the timing of its consequences or vice versa. The perception of the timing of either event is then a weighted average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
150
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(169 citation statements)
references
References 21 publications
17
150
2
Order By: Relevance
“…Indeed, inhibition of this area leads to a ‘weakening’ of IB, which may be interpreted as a decreased sense of control or agency. Moreover, our data support the view of distinct mechanisms underlying action and effect binding (Wolpe et al ., ). Perturbation of pre‐SMA indeed alters only action binding, maintaining unchanged the effect binding: this peculiarity seems to keep participants more focused on their voluntary actions, ignoring however the produced sensory effect.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Indeed, inhibition of this area leads to a ‘weakening’ of IB, which may be interpreted as a decreased sense of control or agency. Moreover, our data support the view of distinct mechanisms underlying action and effect binding (Wolpe et al ., ). Perturbation of pre‐SMA indeed alters only action binding, maintaining unchanged the effect binding: this peculiarity seems to keep participants more focused on their voluntary actions, ignoring however the produced sensory effect.…”
Section: Discussionmentioning
confidence: 97%
“…Being more focused on the voluntary action itself, without considering the produced effects, suggests that SoA might be decreased. The present data could also be discussed in light of the theories underlying the IB process, which demonstrated that action binding, unlike effect binding, is supported by a ‘cue integration theory’ (Wolpe et al ., ). In detail, estimation of time of action depends on an integration of two separate cues: the action and the sensory effect.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We could not measure saliency of events directly in our design, but salient events are known to capture temporal event perception (Wolpe et al, 2013). Importantly, the intentional binding measure that we used as a proxy for sense of agency was entirely independent of the action selection task, and we gave no feedback regarding timing judgments.…”
Section: Discussionmentioning
confidence: 99%
“…Precision is psychologically associated with attentional gain and physiologically with the excitability of neuronal populations reporting prediction errors, resulting in a modulation of perceptual variance. Recently, this view has been proposed as the basis of many neuropsychiatric disorders (Adams, Stephan, et al, 2013;Lawson, Rees, & Friston, 2014;Picard & Friston, 2014;Teufel et al, 2015), in addition to agency-related perceptual or cognitive phenomena (e.g., intentional binding, sensory attenuation, or self-other discrimination (Brown, Adams, Parees, Edwards, & Friston, 2013)), especially in terms of "biased" perceptual variance or precision by priors (Wolpe, Haggard, Siebner, & Rowe, 2013).…”
Section: Bayesian Inference From Perception To Actionmentioning
confidence: 99%